IMPLEMENTASI MANAJEMEN BERBASIS SEKOLAH DALAM MENINGKATKAN PRESTASI BELAJAR PESERTA DIDIK DI SMA MUHAMMADIYAH SUNGGUMINASA KEC. SOMBA OPU KAB. GOWA - ., Surga; ., Armiana (Universitas Islam Negeri Alauddin Makassar, 2022)
The purpose of this study was to determine the implementation of school-based management, the inhibiting and supporting factors as well as the solution in improving the learning achievement of students at SMA Muhammadiyah Sungguminasa Kec. Somba Opu Kab. Gowa. This type of research uses descriptive qualitative research with a phenomenological approach. Methods of data collection using interviews and documentation. The data analysis technique uses data analysis, data presentation and drawing conclusions. The results of the study show that the implementation of school-based management has not been fully implemented properly, caused by the inhibiting factor, namely the financial situation so that it is difficult to procure facilities and infrastructure and their maintenance is also quite apprehensive because they often procure but do not last long for use, student admissions have not met the quota for class capacity. However, it is still supported by educators, the majority of whom have reached a master's education level of around 20%, supported by infrastructure, namely sufficient classes and supported by good teacher cooperation. So that the solution given is holding meetings with parents of students in procuring facilities to support the teaching and learning process, as well as conducting socialization to the school community inviting togetherness in using and maintaining facilities so that they are well controlled, so that they can be used when needed. And continue to socialize to the junior high school level, install student admission announcements openly and introduce the achievements and advantages of the school.